Gestión de ventas en la hacienda agrícola "El Paraíso" Del Cantón Simón Bolívar. - Pretendon Martillo, Ángel Abel (2022)
The present investigation was carried out in the context of the Agricultural Hacienda "El Paraíso", the same one that is located in the Province of Guayas, within the Simon Bolívar Canton, El Arenero Enclosure and that is mainly dedicated to the production and commercialization of bananas. The Hacienda consists of three plots of land: "El Paraiso" with an area of 15 hectares, "El Tesoro" with an area of 5.5 hectares and "La Isla" with an area of 30 hectares. The objective of the research was to analyze how sales are being managed at the Hacienda Agricola "El Paraíso". Among the main aspects found, it was possible to determine that there is good sales management and this is thanks to the strategic alliance that its owner has achieved, as part of the marketing logistics. A negative aspect found is that due to the war between Russia and Ukraine, weekly deliveries of products that go to those two countries are not being cancelled. This research is based on what is established by the Commerce Career of the Faculty of Administration, Finance and Information Technology, for which the line of research was applied: Financial Management, administrative, tax, audit, control. In the same way, since it is a private company that is analyzed, the research subline is involved: Companies and public and private institutions.